2002
DOI: 10.1200/jco.2002.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Sentinel Lymph Node Mapping in Non–Small-Cell Lung Cancer Improves Detection of Micrometastases

Abstract: Intraoperative SN mapping with (99m)Tc is an accurate way to identify the first site of lymphatic tumor drainage in NSCLC. This method may also improve the precision of pathologic staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 25 publications
2
63
1
3
Order By: Relevance
“…Because radioisotopes exhibit a more uniform particle size, various preparations of technetium-99m have been used with regard to pulmonary SLN mapping. Liptay and colleagues intraoperatively injected technetium-99m sulfur colloid and used a hand-held gamma probe to identify highly radioactive nodes [8,9]. Migration time varied considerably, but on average radiocolloid migration was detectable after 10-15 minutes.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Because radioisotopes exhibit a more uniform particle size, various preparations of technetium-99m have been used with regard to pulmonary SLN mapping. Liptay and colleagues intraoperatively injected technetium-99m sulfur colloid and used a hand-held gamma probe to identify highly radioactive nodes [8,9]. Migration time varied considerably, but on average radiocolloid migration was detectable after 10-15 minutes.…”
Section: Commentmentioning
confidence: 99%
“…Several studies have indicated that the SLN accurately reflects the tumor status of regional mediastinal nodes exhibiting greater than 80% accuracy [8][9][10][11]. Present methods of SLN mapping for other organs are, however, not readily amenable for use with respect to staging NSCLC.…”
mentioning
confidence: 99%
“…vidence suggests that, for some types of cancer, lymph fluid and tumor cells from the primary tumor initially flow into a tumor-draining lymph node (LN), 2 the so-called sentinel LN (SLN), before flowing into more distal LNs (1)(2)(3)(4)(5)(6)(7)(8). If correct, then when metastasis is not found in an SLN, it most likely will not be present in more distal nodes; and, in fact, the adverse effects of lymphadenectomy have been avoided in cases of breast cancer (1,2) and melanoma (3,4) based on that idea.…”
mentioning
confidence: 99%
“…Bu prospektif araştırmada mediastinal sentinel lenf nodlarının saptanma oranı %45 olup, Liptay ve arkadaşları mediastinal sentinel lenf nodlarını %22, Nomori ve arkadaşları %35 oranında saptamışlardır (1,5,6,9,13). Çalışmamızda skip drenaj oranının yük-sek olmasının nedeni olgu sayımızın az olması ve %74'ünde tümör lokalizasyonun üst lob yerleşimli olmasıyla açıklanabilir.…”
Section: Discussionunclassified